Reproducibility of auscultatory blood pressure measurement during resistance exercise. - Andrade, Danyele Moura de (2012)
The auscultatory method has been suggested as a viable option for blood pressure (BP) measurement during resistance exercise. However, indicators of reproducibility of this method during resistance exercise have not been established. This study aimed to analyze intra- and inter-examiner reproducibility of auscultatory BP measurements obtained during resistance exercise. Fourteen subjects (24 ± 5 years; 22.0 ± 2.4 kg/m2; systolic BP, 116 ± 7 mmHg; diastolic BP, 75 ± 4 mmHg) performed three sets of 15 repetitions of the knee extension exercise at 50% of their 1-repetition maximum at two different time points (T1 and T2). Before and during exercise, systolic and diastolic BP were measured simultaneously in both arms by two examiners. The intra-examiner intraclass correlation coefficient (ICC) for systolic BP was 0.75 (0.57-0.86) and 0.76 (0.59-0.87) for examiners 1 and 2, respectively. In addition, systolic BP values were similar at T1 and T2 both for examiner 1 (144 ± 9 vs. 146 ± 18, p = 0.08) and examiner 2 (152 ± 9 vs. 153 ± 12, p = 0.32). Inter-examiner ICC was 0.68 (0.46-0.82) for systolic BP and 0.21 (0.11-0.50) for diastolic BP. It can be concluded that auscultatory systolic BP measurement during resistance exercise shows intra- and inter-examiner reproducibility ranging from 0.68 to 0.76, whereas diastolic BP measurement during resistance exercise shows low reproducibility.